Golgi protein 73 and IL-6 as strong predictors of short-term prognosis in patients with HBV-ACLF - Xiaoman Zhang; Jingjing He; Xiangping He; Yongzhi Lun; Caiting He; Zhengju Xu (Scientific Reports)
Abstract To analyze the predictive value of serum Golgi protein 73 (GP73) and IL-6 for 90-day prognosis in patients with hepatitis B virus-related acute-on-chronic liver failure (HBV-ACLF). A total of 289 patients with hepatitis B virus infection who attended the Infection Department of the 910th Hospital of the PLA Logistics Support Force from February 2022 to April 2024 were included in this study. A total of 149 patients with HBV-ACLF were followed up for 3 months after diagnosis, and their outcomes were recorded and assessed. Serum GP73 and IL-6 levels were determined via an enzyme-linked immunosorbent assay and an automatic electrochemical luminescence immunity analyzer, respectively. Multivariate Cox regression, piecewise linear regression analysis, threshold effect and receiver operating characteristic curves were used to evaluate the predictive value of serum Golgi protein 73 (GP73) and IL-6 for 90-day prognosis in patients with HBV-ACLF. Our results revealed that the serum GP73 and IL-6 levels in patients with HBV-ACLF were significantly higher than in chronic hepatitis B group (all P values < 0.001). The serum levels of GP73 and IL-6 in patients with HBV-ACLF who survived after 90 days were lower than those in the nonsurvival group (all P values < 0.001). In addition, the highest serum levels of GP73 and IL-6 were associated with a greater risk of death in HBV-ACLF patients after adjusting for potential confounders (P = 0.0094, 0.0377). Additionally, a nonlinear relationship was observed between GP73 and the risk of 90-day mortality, with an inflection point at 298.99 ng/mL (P = 0.003). A positive linear correlation between IL-6 and the risk of 90-day death was observed in patients with serum IL-6 levels less than 98.78 pg/mL (P = 0.0368). Furthermore, the accuracy of classical prognostic scores, including the model for end-stage liver disease (MELD) score and model for end-stage liver disease-sodium (MELD-Na) score, was significantly improved after combining GP73 and IL-6 in predicting the 90-day prognosis of patients with HBV-ACLF. Serum GP73 and IL-6 levels were significant predictors of short-term prognosis in patients with HBV-ACLF. The combination of GP73 and IL-6 significantly improved the predictive value of classical prognostic scores.